Personalized functional viewpoint of the ITS systems architecture regarding information for users of urban transport systems – a case study for the central city of a metropolis - Grzegorz Karoń; Jerzy Mikulski; Ryszard Janecki (Transport Technologies, 2025)
The article presents a personalized functional view of the ITS architecture concerning Information for users of urban transport systems using the example of ITS systems of the central city of a metropolis. A fundamental issue from the perspective of transport users is obtaining information about the full functional scope of transport systems. Based on such information, it is possible to plan trips in a way that is as efficient as possible for each user individually, and on the other hand, in a sustainable way from the point of view of transport systems and a specific transport policy of the urban/metropolitan area. The choice of such a view is related to the fact that the basic need of the so-called end users of ITS systems, i.e., people moving using transport systems, is to receive valuable and current information in an effective way – preferably in real time, i.e., during the movement of users. The title issue, i.e., personalized functional point of view of the ITS system architecture concerning Information for users of urban transport systems, was presented on the example of ITS systems operating in the central city of an urban agglomeration in Poland with the status of a metropolis. These ITS systems were implemented at the turn of 2023-2024 and were designed using the European ITS framework architecture. The objectives are to identify the current scope of information for users and the current scope of system functions of the examined ITS system to indicate further directions of development of the examined ITS system. Therefore, the characteristics of the connections between the needs of urban transport users and the functions of ITS systems related to Information for these users are presented. Based on such a view of ITS systems, the directions of their further expansion were identified in the functional scope covering the needs of users using urban micromobility and shared transport systems, i.e., car sharing, bike sharing, and electric scooters sharing in journeys planned in real time. The second development area is electromobility, including the development of services related to guiding to parking spaces with electric chargers and planning journeys taking into account the recharging of the traction battery of electric vehicles – passenger cars, delivery vehicles, and trucks.